Albania - Building Competitiveness : Main Report - Overview of Findings and Recommendations - World Bank (World Bank, 2012)
Commitment to structural reforms and to economic stabilization has enabled high rates of gross domestic product (GDP) growth in Albania since the start of transition, and consequent reductions in poverty. The crisis caused by the collapse of 'pyramid' investment schemes in late 1996 and early 1997, the Government began to implement a stabilization and reform program which has resulted in rates of economic growth averaging more than five percent annually between 1998 and 2007. Strong growth has in turn made possible a 6.8 percentage point decline in the poverty headcount, a higher drop than in most countries in the (Eastern) Europe and Central Asia (ECA) region. These achievements have been underpinned by prudent fiscal and monetary policies. Budget deficits have been kept under control, declining from an average of around 10 percent of GDP in the late 1990s to less than 4 percent since 2005. In parallel, a monetary targeting regime has ensured price stability, with inflation remaining at around 3 percent in recent years. This report discusses how Albania can improve its long term competitiveness and growth by facilitating firms' ability to employ technology and skills and by closing the gap between formal regulations and actual enforcement. The second chapter sets the stage by presenting the macroeconomic setting, as well as key structural features of the Albanian economy. The third chapter provides an overview of investment climate constraints on firm performance. The crucial pillars of the investment climate that affect firm performance that is to say: (i) access to and adoption of knowledge by Albanian firms, and (ii) the gap between formal and informal regulation are treated in chapters four and five respectively. Chapter six concludes and summarizes policy recommendations.